2020
DOI: 10.3390/molecules25245866
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography-Tandem Mass Spectrometry for the Simultaneous Analysis of 353 Pesticides in the Edible Insect Tenebrio molitor Larvae (Mealworms)

Abstract: Tenebrio molitor larvae (mealworm) is an edible insect and is considered a future food. Using liquid chromatography-tandem mass spectrometry (LC-MS/MS), a novel method for simultaneous analysis of 353 target analytes was developed and validated. Various sample preparation steps including “quick, easy, cheap, effective, rugged, and safe” (QuEChERS) extraction conditions, number of acetonitrile-hexane partitions, and dispersive-solid phase extraction (dSPE) sorbents were compared, and the optimal conditions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…The dSPE for highly pigmented samples makes use of PSA, GCB and MgSO 4 ; however, in the current study dSPE kits having higher amounts of PSA and C18EC were found be more effective (Dušek et al, 2018;Shin et al, 2020).…”
Section: Methods Optimizationcontrasting
confidence: 67%
See 1 more Smart Citation
“…The dSPE for highly pigmented samples makes use of PSA, GCB and MgSO 4 ; however, in the current study dSPE kits having higher amounts of PSA and C18EC were found be more effective (Dušek et al, 2018;Shin et al, 2020).…”
Section: Methods Optimizationcontrasting
confidence: 67%
“…Application of dynamic MRM scan mode instead of standard MRM mode improved the peak profile, as it helped to focus on specific pesticides at the desired retention times (RTs) only. The dSPE for highly pigmented samples makes use of PSA, GCB and MgSO 4 ; however, in the current study dSPE kits having higher amounts of PSA and C18EC were found be more effective (Dušek et al, 2018; Shin et al, 2020).…”
Section: Resultsmentioning
confidence: 52%
“…A simpler method of sample preparation (followed by liquid chromatography–tandem mass spectrometry (LC-MS/MS)) was used for multi-residue screening of pesticides (including fenpropimorph) in fruit and vegetable samples; the samples were frozen at −20 °C for 24 h and then subjected to cryogenic milling in dry ice [ 24 ]. More recently, LC-MS/MS analyses coupled with modified QuEChERS methods have been used to complement GC/MS when performing multi-residue analyses of pesticides (including fenpropimorph) in insect and plant samples [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Possible contamination by pollutants and pesticide residues derived from their feed is a concern. Our previous studies optimized the analytical method for recovery of several pesticides from Tenebrio molitor larva (mealworms) [ 2 , 3 ]. However, an analytical method has not been developed for pesticide analysis in Protaetia brevitarsis seulensis (white spotted flower chafer).…”
Section: Introductionmentioning
confidence: 99%
“…In combination with liquid chromatography tandem mass spectrometry (LC-MS/MS) and gas chromatography tandem mass spectrometry (GC-MS/MS), modified QuEChERS (quick, easy, cheap, effective, rugged, and safe) methods have been reported for extraction of pesticide multiresidues from different type of matrices [ 12 14 ]. Many studies used a single sorbent, sorbent mixture, and low-temperature precipitation to effectively eliminate fat and lipids from a wide range of fatty samples such as avocado [ 15 ], edible insects [ 2 , 3 ], meat [ 16 ], honey bees [ 17 ], peanut oil [ 18 ], soybean-based products [ 19 ], and vegetable oils [ 20 ]. Our previous study used low temperature precipitation (-20°C) to remove large amount of fat and lipids derived from mealworms to analyze fenoxanil, deltamethrin, and chlorpyrifos [ 2 ].…”
Section: Introductionmentioning
confidence: 99%